Biological and ecological factors related to trace element levels in harbour porpoises (Phocoena phocoena) from European waters - Lahaye, Virginie; Bustamante, Paco; Law, Robin; Learmonth, J.; Santos, Maria; Boon, Jan; Rogan, Emer; Dabin, Willy; Addink, Marian; Lopez, Alfredo; Zuur, Alan; Pierce, Graham; et al. (Marine Environmental Research, 2007)
International audience Selected trace elements (Cd, Cu, Hg, Se, Zn) were measured in the kidneys and the liver of 104 harbour porpoises (Phocoena phocoena) stranded along the coasts of France, Galicia (Spain), Ireland, Scotland (UK), and the Netherlands. Generally, relatively low concentrations of toxic elements were encountered in the tissues of European porpoises, except for two individuals, which displayed high hepatic Hg concentrations. Also, elevated Cd levels obtained in Scottish porpoises could be related to their feeding preferences and this result suggests an increase of the proportion of cephalopods in their diet with latitude. Moreover, significant geographical differences were seen in hepatic Zn concentrations; the elevated Zn concentrations displayed by porpoises from the Netherlands may relate their poor health status. Variation in metal concentrations within porpoises from the North Sea is likely to reflect a long-term segregation between animals from northern (Scotland) and southern areas (the Netherlands), making trace elements powerful ecological tracers.